Contralateral inclinatory approach for decompression of the lateral recess and same-level foraminal lesions using unilateral biportal endoscopy: A technical report - Tian, Dasheng; Zhu, Bin; Liu, Jianjun; Chen, Lei; Sun, Yisong; Zhong, Huazhang; Jing, Juehua (Frontiers in Surgery, 2022)
Objective: Unilateral biportal endoscopic（UBE）surgery is increasingly adapted as a minimal invasive technique.The purpose of the current study was to introduce a novel surgical technique for lateral recess and adjacent level foraminal decompression by contralateral inclinatory approach with unilateral biportal endoscopy（CIA-UBE）at the lumbar level. Methods: Between January 2020 to February 2022, 10 patients suffering from lateral recess and adjacent level foraminal stenosis at the lumbar level were underwent UBE surgery by contralateral inclinatory approach（CIA-UBE）. Magnetic resonance imaging (MRI) scan was checked after surgery to measure the cross-sectional area (CSA) of spinal canal (CSA-SC)，cross-sectional area of the intervertebral foramen(CSA-IVF) and facet joint(CAS-FJ) . Postoperative radiologic images computed tomography (CT) were obtained to investigate existence of facet joint violation.Clinical outcomes were assessed by Oswestry Disability Index (ODI)scores and visual analogue scale (VAS) scores of buttocks and radicular pain. Results: 10 levels were decompressed, the mean age of the patients was 56.92 ± 13.26 years. The mean follow-up periods were 7.60 ± 4.47 months. The average operative time were 85.14 ± 25.65 minutes. Postoperative CT and MRI revealed ideal neural decompression of the treated segments in all patients. CSA-IVF and CSA-FJ improved significantly indicating good foraminal and lateral recess decompression with less damage to facet joint. Preoperative VAS and ODI scores improved significantly after the surgery. Conclusion: CIA-UBE may be an effective surgical treatment of the lateral recess and adjacent level foraminal stenosis at the lumbar level, which provides successful surgical decompression for traversing or（and）exiting nerve roots with better operative view and more easy surgical manipulation. This approach may also help to maximize the preservation of the facet joint.